Animal development, liver histology, and antioxidant activity in the muscle of zebrafish (Danio rerio) fed with natural additives in the diets (Research, Society and Development, 2022)
This work was carried out to evaluate the animal development, liver histology, and antioxidant effects on zebrafish fed with natural additives in different levels. Natural additives were composed by Baccharis dracunculifolia extract, cashew nut shell liquid (CNSL), and clove leaf essential oil (CLEO). The groups were: CONT: basal diet without the addition; CONB: addition of 50 g BHT kg-1 feed; MIX1: addition of 50 g of natural additives kg-1 feed (60% B. dracunculifolia, 39% CNSL, and 1% CLEO); MIX2: addition of 50 g of natural additives kg-1 feed (70% B. dracunculifolia, 29% CNSL, and 1% CLEO); MIX3: addition of 50 g of natural additives kg-1 feed (90% B. dracunculifolia, 9% CNSL, and 1% CLEO); and MIX4: addition of 50 g of natural additives kg-1 feed (99% B. dracunculifolia, 0.9% CNSL, and 0.1% CLEO). The average daily gain was lower for fishes fed the MIX4 diet. Diets effect was observed in liver histology (P < 0.001), which were greater in fishes fed CONB and MIX4 diets. Antioxidant activity in the diet evaluated using the ABTS assay was greater (P < 0.05) for treatments with natural additives. Similarly, antioxidant activity in zebrafish muscle (P < 0.05). Thus, the inclusion of 5% of natural additives in the diet composed by B. dracunculifolia extract, CNSL, and CLEO improved the antioxidant activity of zebrafish muscle.